Further research on the biological function of inclusion bodies of Anomala cuprea entomopoxvirus, with special reference to the effect on the insecticidal activity of a Bacillus thuringiensis formulation. Issue 1 (26th April 2013) - Mitsuhashi, Wataru; Asano, Shoji; Miyamoto, Kazuhisa; Wada, Sanae
Abstract Background Entomopoxviruses (EVs) form two types of inclusion body: spheroids, which contain virions, and spindles, which do not. The authors tested whether the spindles from a coleopteran EV, Anomala cuprea EV (ACEV), enhanced the insecticidal activity of a commercial Bacillus thuringiensis (Bt) formulation and the susceptibility of scarabaeid pest species in Japan to the virus's spheroids, to assess whether ACEV inclusion bodies are potential biological control agents for pest insects. Results Peroral inoculation with both ACEV spindles and the Bt toxin only or the complete Bt formulation shortened the survival and increased the mortality of treated insects compared with those of insects inoculated with Bt without the spindles (8–38 h of decrease in LT50 values among assays). ACEV showed high infectivity to a major scarabaeid pest species in Japanese sugar cane fields. Conclusion The results suggest that spindles or the constituent protein fusolin can be used as a coagent with Bt formulations, and that fusolin coexpression with a Bt toxin in crops might improve the insecticidal efficacy. In addition, the spheroids are potential biocontrol agents for some scarabaeid pests that are not easy to control because of their underground habitation. © 2013 Society of Chemical Industry